IMPROVING STUDENTS’ WRITING ACHIEVEMENT IN DESCRIPTIVE TEXT THROUGH TASK BASED LANGUAGE TEACHING (TBLT) (A CLASSROOM ACTION RESEARCH AT THE STUDENTS OF CLASS VII-E SMPN 01 BATU) - OKTAVIANTI, EKA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key words: Writing Achievement, TBLT, Decriptive Text Writing is one of the basic skills that have to be learnt by students in junior high school. In the first year of junior high school the students are expected to be able to develop and produce simple functional text, like descriptive text. Based on the preliminary study that has been conducted by the researcher, it was showed that most of VII-E students in SMPN 01 Batu have difficulties in writing descriptive text. So,the aim of this research is to improve students’ writing ability in descriptive text using TBLT at the seventh grades of SMPN 01 Batu.The method of this research is Classroom Action Research (CAR). This research was conducted  in two cycles  and each cycle consisted of four steps, they were: Planning, action, observation, and reflection. Each cycle was conducted in two meetings, so the researcher conducted this research in two weeks. To collect and analyze the data, the researcher used the information from qualitative (interview, observation, and questionnaire) and quantitative data (the students’ achievement in pre-test and post-test) in order to support the data collected.The result of this researcher reveals that TBLT method can improve their writing’s ability in descriptive text. The students’ responses show that they were interested to learn writing subject because they felt easier to write and enjoy the process of writing using TBLT. The students’ mean score in pre test was 71,40. In the first cycle the mean score was 83,39. Meanwhile the mean score in the second cycle was 87,10. It means that there was 16,79 % of mean improvement from the students’ score in the preliminary study to the first cycle and there was 21,98% of mean score improvement from the students’ score in preliminary study to the second cycle and also improvement in each aspects of writing descriptive text. From this result, the researcher concludes that teaching descriptive writing using TBLT at the seventh grades of students at SMPN 01 Batu can improve their writing ability.The researcher suggests the school to facilitate the teacher in learning TBLT and applyingTBLT in teaching and learning process. She also suggest for  students to keep practicing writing and for further researchers to do similar research using TBLT to improve students’ writing ability with more various and challenging task.